2019
DOI: 10.1108/ilt-07-2018-0265
|View full text |Cite
|
Sign up to set email alerts
|

Using recurrence plots for stability analysis of ring-on-disc tribopairs

Abstract: Purpose AISI 52100-AISI 1045 specimens were used as the ring-on-disc tribopairs in the experiments to investigate the stability of friction process. Design/methodology/approach The coefficient of friction (COF) signals were measured throughout the friction process and the recurrence plots (RPs) and recurrence quantification analysis (RQA) are adapted to analyze the stability of the tribosystem. Findings The results show that the COF time-series acquired from different tests possess the same dynamic evoluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…For example, Ding et al [13,14] utilized the correlation dimension to monitor wear state changes while proposing a new characteristic parameter called moving cut data-approximate entropy that accurately identifies the wear state during friction. Sun et al [15] found that recurrence plots and recurrence quantification analysis can be used to characterize each stage of the friction process. Zhou et al [16] researched the chaos properties of the friction temperature during friction.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Ding et al [13,14] utilized the correlation dimension to monitor wear state changes while proposing a new characteristic parameter called moving cut data-approximate entropy that accurately identifies the wear state during friction. Sun et al [15] found that recurrence plots and recurrence quantification analysis can be used to characterize each stage of the friction process. Zhou et al [16] researched the chaos properties of the friction temperature during friction.…”
Section: Introductionmentioning
confidence: 99%